PENERAPAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN SISWA SMP MATERI PEMISAHAN CAMPURAN - Riya Sari Oktaviani; Rosdiana, Laily (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes and student activeness in science learning, particularly on the topic of separation of mixtures in junior high school. Preliminary observations showed that the average student score was 65, which had not reached the Minimum Mastery Criteria (KKTP) of 78, and student participation during learning activities was still low. Therefore, this study aimed to describe the implementation of learning, student learning outcomes, student activeness, and student responses after the application of the guided inquiry learning model. This research employed a pre-experimental design using a one-group pretest–posttest approach. The study was conducted at SMP Negeri 2 Krian Sidoarjo with students of class VIII-A as the research subjects. Data were collected through tests, observations, and questionnaires using several instruments, including observation sheets for learning implementation, observation sheets for student activeness, pretest and posttest questions covering cognitive aspects (C2–C4), and student response questionnaires. The data were analyzed descriptively using the mode value to determine the implementation of learning, the N-gain score to measure the improvement of learning outcomes, percentage analysis to determine student activeness, and Likert and Guttman scale interpretations to analyze student responses. The results showed that the implementation of learning was categorized as very good. Student learning outcomes increased with moderate to high N-gain categories, student activeness improved particularly in science process skill indicators, and student responses toward the learning process were categorized as very positive. These findings indicate that the guided inquiry learning model is effective in improving student learning outcomes and activeness in science learning on the topic of separation of mixtures